2021
DOI: 10.1177/14613484211032757
|View full text |Cite
|
Sign up to set email alerts
|

Study on the nonlinear vibration of embedded carbon nanotube via the Hamiltonian-based method

Abstract: This article mainly studies the vibration of the carbon nanotubes embedded in elastic medium. A new novel method called the Hamiltonian-based method is applied to determine the frequency property of the nonlinear vibration. Finally, the effectiveness and reliability of the proposed method is verified through the numerical results. The obtained results in this work are expected to be helpful for the study of the nonlinear vibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Due to these unprecedented advantages, the formulation caught immediate attention after publication due to its extremely simplicity and remarkable reliability. It has been successfully applied to Kundu-Mukherjee-Naskar oscillator [27], nonlinear vibration of embedded carbon nanotube [28], fractal vibration systems [29,30], packaging systems [31] and MEMS oscillators [32]. It has been hailed as an unprecedented success.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these unprecedented advantages, the formulation caught immediate attention after publication due to its extremely simplicity and remarkable reliability. It has been successfully applied to Kundu-Mukherjee-Naskar oscillator [27], nonlinear vibration of embedded carbon nanotube [28], fractal vibration systems [29,30], packaging systems [31] and MEMS oscillators [32]. It has been hailed as an unprecedented success.…”
Section: Introductionmentioning
confidence: 99%
“…( ) Various nonlinear systems in physics, mechanics and engineering can be modeled as a nonlinear oscillator with an odd restoring force function. The vibration of carbon nanotubes embedded in elastic medium [64], and the nonlinear vibration of bi-directional functionally grade beams [8] are two wellknown examples. Equation (1) can be rewritten in terms of the independent variable t w = t as follows:…”
Section: Solution Proceduresmentioning
confidence: 99%
“…The real train test showed that the vertical vibration of the power pack frame was reduced by 55.77% after the particle damper was added, and the vibration reduction effect under other conditions was 51.83%. Wang Jinchao et al [58] designed particle damping and constrained damping to solve the problem of abnormal vibration of carbon slide of subway pantograph. Through comparison of test results, particle damping has stronger vibration suppression effect under transverse excitation condition.…”
Section: Application Analysis Of Particle Damped Rail Transitmentioning
confidence: 99%